Intraocular Lymphoma: Descriptive Data of 26 Patients Including Clinico-pathologic Features, Vitreous Findings, and Treatment Outcomes. (3rd April 2018) - Abu Samra, Khawla; Oray, Merih; Ebrahimiadib, Nazanin; Lee, Stacey; Anesi, Stephen; Foster, C. Stephen
ABSTRACT: Purpose : To describe clinical manifestations, diagnostic approaches, therapy, and outcomes of biopsy-proven intraocular lymphoma. Methods : Review of tertiary referral center records between 2005 and 2015. Results : A total of 51 eyes of 26 patients were included; mean age of onset was 60.42 years. Common ocular complaints included floaters (42%) and blurred vision (35%); 62% of patients had ocular and central nervous system involvement; 11% had systemic lymphoma; and 27% had only ocular involvement. Vitreous analysis was positive for malignant cells in 77% of patients on initial biopsy, and in 100% of patients on repeat biopsy. In total, 20/26 patients received systemic and topical treatment before IOL diagnosis was made; 25 patients received intravitreal methotrexate and/or rituximab; one patient received intracameral rituximab. All patients achieved remission by their final visit. Conclusions : Intraocular lymphoma often masquerades as intraocular inflammation, resulting in delayed or misdiagnosis with subsequent inappropriate management. Optimal therapy is a challenge for oncologists and ophthalmologists.